Beyond Prison Walls: A Case Study - Darryl Henderson (Adult Education Research Conference, 2010)
This study was an investigation into adolescent male’s perception of parenting styles and their ability to cope with problematic experiences and attachment to parents/caregivers and peers, with emphasis on one inmate (WC) in particular, who was the subject of a case study. All of the adolescents in this study were all at- risk for incarceration given their problem behavior and prior affiliation with the juvenile justice system with the exception of WC, who spent sixteen years in prison. Study participants subjects were administered the Parental Authority Questionnaire (PAQ), the Inventory of Parent and Peer Attachment (IPPA) and the Adolescent Coping Orientation for Problem Experiences ( A-COPE). Study findings revealed correlations between parenting style, attachment and coping for adolescents with a history of incarceration or those who are at-risk for incarceration. Likewise, a solid attachment to a parental figure, a healthy personal constitution and an array of social supports can significantly reduce recidivism and can be very instrumental in one’s adjustment to society post incarceration.